Clinical relevance of bacterial and/or viral coinfection in acute bronchiolitis in an Italian neonatal unit during the 2021–2023 seasons - Cortazzo, Venere; Agosta, Marilena; De Rose, Domenico Umberto; Fox, Valeria; Di Maio, Velia Chiara; Vrenna, Gianluca; Rossitto, Martina; Lucignano, Barbara; Ranno, Stefania; Sisto, Annamaria; Russo, Cristina; Braguglia, Annabella; et al. (Frontiers in Pediatrics, 2025)
BackgroundAcute bronchiolitis is a leading cause of hospitalization in young children worldwide, and literature reports conflicting data regarding the role of coinfections.ObjectiveTo evaluate the possible clinical relevance of bacterial and/or viral respiratory coinfection in a cohort of newborns/infants hospitalized for bronchiolitis.MethodsNeonates and infants younger than three months admitted to neonatal units from October 2021 to March 2023 because of acute bronchiolitis were included in this retrospective study. Analyses were performed with Stata 11.1 (p < 0.05). Data were summarized as medians (IQR) or counts (%). Appropriate tests were used based on data type and distribution, with Benjamini–Hochberg correction for multiple comparisons. Odd Ratios (ORs) were unadjusted.ResultsIn a cohort of 240 patients, respiratory coinfection was associated with a longer hospital stay (p < 0.001) and the need for invasive mechanical ventilation (p < 0.001) compared to viral mono-infection, highlighting a potential role in patient outcome. Moreover, we observed that premature patients are more likely to contract a respiratory coinfection than a viral mono-infection (p = 0.011).ConclusionCoinfections increased the clinical severity of bronchiolitis more than simple viral mono-infection in our cohort, contributing to a longer hospital stay and the need for invasive mechanical ventilation.